Integrated CYP2D6 interrogation for multiethnic copy number and tandem allele detection. (6th December 2018) - Qiao, Wanqiong; Martis, Suparna; Mendiratta, Geetu; Shi, Lisong; Botton, Mariana R; Yang, Yao; Gaedigk, Andrea; Vijzelaar, Raymon; Edelmann, Lisa; Kornreich, Ruth; Desnick, Robert J; Scott, Stuart A
Aim: To comprehensively interrogate CYP2D6 by integrating genotyping, copy number analysis and novel strategies to identify CYP2D6*36 and characterize CYP2D6 duplications.Methods: Genotyping of 16 CYP2D6 alleles, multiplex ligation-dependent probe amplification (MLPA) and CYP2D6*36 and duplication allele-specific genotyping were performed on 427 African–American, Asian, Caucasian, Hispanic, and Ashkenazi Jewish individuals.Results: A novel PCR strategy determined that almost half of all CYP2D6*10 (100C>T) alleles are actually *36 (isolated or in tandem with *10 ) and all identified duplication alleles were characterized. Integrated results from all testing platforms enabled the refinement of genotype frequencies across all studied populations.Conclusion: The polymorphic CYP2D6 gene requires comprehensive interrogation to characterize allelic variation across ethnicities, which was enabled in this study by integrating multiplexed genotyping, MLPA copy number analysis, novel PCR strategies and duplication allele-specific genotyping.